2010
DOI: 10.1080/01634372.2010.488280
|View full text |Cite
|
Sign up to set email alerts
|

A Lesbian Older Adult Managing Identity Disclosure: A Case Study

Abstract: The aim of this study was to explore the experience of an older lesbian in managing the disclosure of her sexual identity. Specifically, the team wanted to better understand the ways she managed her identity in an assisted living facility. Using a qualitative case study methodology, 2 in-depth interviews were conducted. The following 5 themes were identified in the data: keeping her own counsel, maintaining "family" connection, celebrating second chances, living outside the L box, and staying morally centered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…There is a growing social work literature on the experiences of older LGBT people (Hughes, 2009a;Hughes 2009b;Jenkins, Walker, Cohen, & Curry, 2010;Lee & Quam, 2013;McGovern, 2014;Quam, Whitford, Dziengel, & Knochel, 2010;Rowan & Giunta, 2014;Van Sluytman & Torres, 2014;Ward, Rivers, & Sutherland, 2012) as well as literature aimed at enabling social work practitioners to work more holistically with older LGBT service users (Erdley, Anklam, & Reardon, 2014;Fredriksen-Goldsen, Hoy-Ellis, Goldsen, Emlet, & Hooyman, 2014;Gratwick, Jihanian, Holloway, Sanchez, & Sullivan, 2014;Portz et al, 2014;Stonewall, 2012;Westwood, King, Almack, & Suen, 2015). However both bodies of literature are predominantly based on the experiences of older gay men and, to a lesser extent, older lesbians, meaning that little can be deduced about the distinctive experiences of transgender and bisexual people (Barker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing social work literature on the experiences of older LGBT people (Hughes, 2009a;Hughes 2009b;Jenkins, Walker, Cohen, & Curry, 2010;Lee & Quam, 2013;McGovern, 2014;Quam, Whitford, Dziengel, & Knochel, 2010;Rowan & Giunta, 2014;Van Sluytman & Torres, 2014;Ward, Rivers, & Sutherland, 2012) as well as literature aimed at enabling social work practitioners to work more holistically with older LGBT service users (Erdley, Anklam, & Reardon, 2014;Fredriksen-Goldsen, Hoy-Ellis, Goldsen, Emlet, & Hooyman, 2014;Gratwick, Jihanian, Holloway, Sanchez, & Sullivan, 2014;Portz et al, 2014;Stonewall, 2012;Westwood, King, Almack, & Suen, 2015). However both bodies of literature are predominantly based on the experiences of older gay men and, to a lesser extent, older lesbians, meaning that little can be deduced about the distinctive experiences of transgender and bisexual people (Barker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of those described, 48% of participants were male and 52% female. Four studies reported on participants' ethnicity (Brown, Reavey, Kanyeredzi, & Batty, 2014;Jenkins, Walker, Cohen, & Curry, 2010;McCann, 2000;Stein et al, 2010). Due to inconsistent reporting, overall participant demographics could not be summarised.…”
Section: Resultsmentioning
confidence: 99%
“…Some gay and lesbian participants harboured fears about disclosing their sexuality (Jenkins et al, 2010;Röndahl et al, 2006;Stein et al, 2010): (Quinn & Happell, 2015a, p.125).…”
Section: Hopes and Fearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges or disruption caused by marginalisation has seen lesbian women develop resilience (Jenkins et al . ) or a substantial capacity to bounce‐back , and this coping mechanism is referred to in the literature as crisis competence (Kimmel ). Further, the development of crisis competence empowers lesbian women to shield themselves against the challenges associated with ageing (McCann et al .…”
Section: Introductionmentioning
confidence: 99%